Methodological Issues on Planning and Running the Brazilian Multicenter Study on Preterm Birth - Giuliane J. Lajos; Ricardo P. Tedesco; Renato Passini; Tabata Z. Dias; Marcelo L. Nomura; Patrícia M. Rehder; Samira M. Haddad; Maria H. Sousa; Jose G. Cecatti; Brazilian Multicenter Study on Preterm Birth Study Group (The Scientific World Journal)
Objectives. Assuming that the occurrence of preterm births and their maternal and neonatal associated conditions in Brazil are not completely known, a multicenter study was proposed. The purpose of this paper is to describe the methods used, its processes, achievements, and challenges. Study Design. A multicenter cross-sectional study on preterm births in Brazilian facilities plus a nested case-control study to assess their associated factors. A description of all steps of planning and implementing such a nationwide study, including strategies for dealing with problems arising during the process, is presented. Results. 20 referral hospitals in different regions of Brazil participated in the study. A detailed questionnaire for data collection, an electronic platform for data transcription and monitoring, research materials, and specific monitoring tools were developed; then data management and analyses were performed. Finally, we got information on 4,150 preterm births and 1,146 term births. Conclusions. This study represented the first step of a planned comprehensive assessment of preterm birth in Brazil, with detailed information that will lead to several analyses and further studies, bringing the knowledge to improve screening, diagnosis, and treatment practices in maternal and perinatal health with the final purpose of reducing the burden of this condition in the country.